Modeling Biometric Traits, Yield and Nutritional and Antioxidant Properties of Seeds of Three Soybean Cultivars Through the Application of Biostimulant Containing Seaweed and Amino Acids - Kocira, Sławomir; Szparaga, Agnieszka; Kocira, Anna; Czerwińska, Ewa; Wójtowicz, Agnieszka; Bronowicka-Mielniczuk, Urszula; Koszel, Milan; Findura, Pavol (Frontiers in Plant Science, 2018)
In recent years, attempts have been made to use preparations that allow obtaining high and good quality yields, while reducing the application of pesticides and mineral fertilizers. These include biostimulants that are safe for the natural environment and contribute to the improvement of yield size and quality, especially after the occurrence of stressors. Their use is advisable in the case of crops sensitive to such biotic stress factors like low temperatures or drought. One of these is soybean which is a very important plant from the economic viewpoint. Field experiments were established in the years 2014-2016 in a random block design in four replicates on experimental plots of 10 m2. Three soybean cultivars: Annushka, Mavka, and Atlanta were planted in the third decade of April. Fylloton biostimulant was used at 0.7% or 1% concentrations as single spraying (BBCH 13-15) or double spraying (BBCH 13-15, BBCH 61) in the vegetation period. The number of seeds per 1 m2, seed yield, thousand seed weight, number of pods per plant, number of nodes in the main shoot, height of plants, and protein and fat contents in seeds were determined. The content of phenolic compounds, antioxidant capacity and antioxidant effect of soybean seeds were assayed as well. Foliar treatment of soybean with Fylloton stimulated the growth and yield of plants without compromising their nutritional and nutraceutical properties. The double application of the higher concentration of Fylloton was favorable for the plant height, seed number and soybean yield. Moreover, the highest number of pods was obtained after single treatment of plants with the lower biostimulant concentration. There was also a positive effect of using this biostimulant on the content and activity of some bioactive compounds, such as phenolics and flavonoids, and on the reducing power.